Functional characterization of Dihydroflavonol-4-reductase in anthocyanin biosynthesis of purple sweet potato underlies the direct evidence of anthocyanins function against abiotic stresses. - Hongxia Wang (Public Library of Science (PLoS), 2013)
Dihydroflavonol-4-reductase (DFR) is a key enzyme in the catalysis of the stereospecific reduction of dihydroflavonols to leucoanthocyanidins in anthocyanin biosynthesis. In the purple sweet potato (Ipomoea batatas Lam.) cv. Ayamurasaki, expression of the IbDFR gene was strongly associated with anthocyanin accumulation in leaves, stems and roots. Overexpression of the IbDFR in Arabidopsis tt3 mutants fully complemented the pigmentation phenotype of the seed coat, cotyledon and hypocotyl. Downregulation of IbDFR expression in transgenic sweet potato (DFRi) using an RNAi approach dramatically reduced anthocyanin accumulation in young leaves, stems and storage roots. In contrast, the increase of flavonols quercetin-3-O-hexose-hexoside and quercetin-3-O-glucoside in the leaves and roots of DFRi plants is significant. Therefore, the metabolic pathway channeled greater flavonol influx in the DFRi plants when their anthocyanin and proanthocyanidin accumulation were decreased. These plants also displayed reduced antioxidant capacity compared to the wild type. After 24 h of cold treatment and 2 h recovery, the wild-type plants were almost fully restored to the initial phenotype compared to the slower recovery of DFRi plants, in which the levels of electrolyte leakage and hydrogen peroxide accumulation were dramatically increased. These results provide direct evidence of anthocyanins function in the protection against oxidative stress in the sweet potato. The molecular characterization of the IbDFR gene in the sweet potato not only confirms its important roles in flavonoid metabolism but also supports the protective function of anthocyanins of enhanced scavenging of reactive oxygen radicals in plants under stressful conditions.